DIELECTRIC RELAXATION IN POR-SI LAYERS AT LOW FREQUENCIES - Yu.M. Spivak; R.A. Castro; M.P. Sevryugina; M.A. Kuznetsova; V.A. Moshnikov (Физико-химические аспекты изучения кластеров, наноструктур и наноматериалов, 2020)
Macroporous silicon with a mesoporous nanostructured surface layer on its top was obtained by a method of electrochemical anodic etching. The frequency dependences of the dielectric coefficients for porous Si layers were measured in the frequency range 5∙10^(-3) < f < 10^6 Hz at a temperature of 295 K and an applied voltage of 1 V. A maximum of the dielectric loss tangent is revealed, which is most likely due to the predominance of the dipole relaxation mechanism of polarization. The distribution of relaxers over relaxation times has been. An interpretation of the results obtained from the point of view of the structure of the porous layer is proposed.